2006
DOI: 10.1515/ijdhd.2006.5.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality for interactive binocular treatment of amblyopia

Abstract: Amblyopia, or 'lazy eye', is currently treated by wearing an adhesive patch over the non-amblyopic eye for several hours per day, over a period of many months. Non-compliance with patch wearing is a significant problem. Our multi-displinary team involved clinicians and technologists to investigate the application of virtual reality technology in a novel way. We devised a binocular treatment system in which children watch a video clip of a cartoon on a virtual TV screen, followed by playing an interactive compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…In our study, I-BiT™ was found as an effective complementary method for amblyopia treatment like other studies 12, 13, 15, 16, 17. The mean of BCVA was increased in two groups significantly with more improvement in cases who received both I-BiT™ and patching therapy simultaneously.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…In our study, I-BiT™ was found as an effective complementary method for amblyopia treatment like other studies 12, 13, 15, 16, 17. The mean of BCVA was increased in two groups significantly with more improvement in cases who received both I-BiT™ and patching therapy simultaneously.…”
Section: Discussionsupporting
confidence: 69%
“…Therefore, our cases received I-BiT™ as a complementary treatment to occlusion, unlike the previous studies which compared I-BiT™ with occlusion in separate groups 12, 13, 15, 16, 17…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that video games can be very useful for visual rehabilitation [1]. Classical examples of games found in literature, include PAC-MAN and simple car racing games [8]. In this work we propose a simple car racing game.…”
Section: Rehabmentioning
confidence: 99%